Mexidol, Cytoflavin, and succinic acid derivatives as antihypoxic, anti-ischemic metabolic modulators, and ergogenic aids in athletes and consideration of their potential as performance enhancing drugs - Jędrejko, Karol; Catlin, Oliver; Stewart, Timothy; Muszyńska, Bożena (Drug testing and analysis, 2024)
Emoxypine (ethylmethylhydroxypyridine) is a synthetic derivative of vitamin B . Emoxypine succinate is a registered drug in Russia and Ukraine under various trade names including Mexidol, Mexicor, and Armadin Long. Mexidol demonstrates antihypoxic and anti-ischemic effects and also modulates metabolism. The use of Mexidol by Russian athletes has been confirmed in the past. Current use by athletes is unknown as this drug is not monitored or included in drug testing protocol. Metabotropic and antihypoxic effects of Mexidol were compared to the effects of meldonium or trimetazidine, both of which are included on the World Anti-Doping Agency (WADA) Prohibited List in category S4.4. Metabolic Modulators. The conjugation of emoxypine with succinate elevates the therapeutic effectiveness of the Mexidol formulation as succinic acid itself has important impacts to consider despite being a common food additive and drug excipient. Other succinic acid salts like ammonium succinate, found as dietary supplement, have been patented as performance enhancers. Available research on healthy subjects suggests that combinations of selected 3-substituted pyridine derivatives with succinate including Mexidol and a related drug Cytoflavin can enhance the performance of athletes. Cytoflavin is a multi-component formula containing meglumine sodium succinate, nicotinamide (vitamin B ), inosine (riboxin), and riboflavin. Other related succinate-based drugs include Remaxol, Reamberin, and Cogitum. Mexidol and Cytoflavin and related substances exhibit similar biological effects as drugs on the WADA Prohibited List, and if they are used for performance enhancement by athletes, they could be worthy of consideration as prohibited substances in sport.